The Psychological Dimensions of the Story of Prophet Yusuf in Tafsir Al-Azhar by Buya Hamka - Nazli Badrul Aini Ramdhani; Uqbatul Khair Rambe (Jurnal test, 2025)
This study aims to examine the psychological dimension of the story of the Prophet Yusuf based on Buya Hamka’s interpretation in the Tafsir Al-Azhar because the story of the Prophet Yusuf in the Qur’an is a narrative full of meaning, not only theologically and morally, but also has a deep psychological dimension. The study was conducted with an interpretive approach, considering that the main object of the study is the text of the Qur’an and its interpretation, which is normative and requires contextual understanding. The primary data sources in this study are the Qur’an, especially Surah Yusuf, and the Tafsir Al-Azhar by Buya Hamka. Meanwhile, secondary data were obtained from various relevant literature, such as Islamic psychology books, thematic interpretations, scientific journals, articles, and other written works. The results of the study show that the Al-Azhar Interpretation presents the story of the Prophet Yusuf as a medium for psychological education that is relevant to the context of modern life, particularly in building mental resilience, emotional control, and spiritual therapy. This study is expected to enrich the treasure trove of thematic interpretations with an Islamic psychological perspective. It is concluded that the story of the Prophet Yusuf contains a rich and profound psychological dimension. Buya Hamka successfully interpreted the story not only from a legal and moral perspective, but also from the psychological conditions of its characters. The psychological dimensions that emerge include the jealousy of Yusuf’s brothers, Yusuf’s mental fortitude, Zulaikha’s inner turmoil, the temptation of women, and the process of regret and forgiveness. Buya Hamka positions the story of the Prophet Yusuf as a medium for spiritual therapy for humans undergoing trials, as well as moral and psychological education that can be applied in modern life.